Youth athletes' developmental outcomes by age, gender, and type of sport - Kilic, K.; Ince, M. L. (Journal of Human Sport & Exercise, 2021)
The purpose of this study was to examine the athletes` perceived developmental outcomes of competence, confidence, connection and character (the 4 Cs) in a competitive youth sport context with respect to age groups (12 - 14 vs 15 - 18-year-old), gender (girls and boys) and sport type (individual vs. team). Participants were 314 athletes (173 girls, 141 boys) and 31 coaches (5 Women, 26 Men) from artistic gymnastics, basketball, football, swimming, tennis, track and field, and volleyball. Data were collected by the adapted and validated form of Positive Youth Development Measurement Toolkit. According to the findings, older group of athletes (15 - 18 years of age) had lower scores than their younger counterparts (12 - 14 years of age) in all of the developmental outcomes. Girls scored lower in competence outcome, while boys had lower scores in connection and character outcomes. Moreover, team sport athletes had lower scores in competence outcome (p < .05). The findings were discussed with the extant literature, and programmatic suggestions for future studies were provided.